Traditional and modern agroforestry in the Mediterranean Basin - Pardini, Andrea; Pratesi, Valentina; Paterniani, Maria Lidia Stipp [UNESP] (My University, 2010)
The Mediterranean Basin has been the cradle of many civilizations that have gradually introduced crops, animal breeds and agricultural techniques. The variability of land and resources has interacted for centuries and the present result is a fragmented mosaic of land uses and, frequently, complex agro-silvo-pastoral systems. Agriculture and forestry in the Mediterranean Basin are traditionally linked with livestock rearing, but the integration of resources has been reduced after the second world war on benefit of intensive and specialized farming systems. The long period of intensive agriculture has caused environmental problems and need to sustain yields with higher and higher inputs, consequently concern for environmental protection and biodiversity conservation was risen and many farms started more environmental friendly practices that include new association of trees, crops and pastures. In the last two decades there is a renewed interest for the integration of woody and herbaceous resources and for extensive animal rearing that make use also of specialized crops, crop residuals, forest grazing, grass grazing in tree plantations, the result in many farms has been the formation of complex agro-silvo-pastoral systems. The complexity of the systems reduces farm efficiency because of the more difficult management, however improves the ecological stability, sustainability of productions over long periods and, moreover, favours the valorisation of the diversities of the territory with tourism. The larger number of resources and higher complexity of the new systems in comparison to specialized and simplified farming systems help the integration of conventional agriculture with different sectors of the economy, like agro-tourism. An outlook of the main forest species associated with crops and pasture is given with a discussion of management of agro-silvo-pastoral systems in the countries of the Mediterranean Basin. A brief discussion of conventional agronomic tools more effective in northern and southern areas is given. A simple classification of systems variability is proposed as it is functional also to plan further changes in resources management. Finally new possibilities of valorisation of rural areas through complex and integrated agro-silvopastoral systems are introduced. © 2010 by Nova Science Publishers, Inc. All rights reserved.